The power of words: Exploring language and communication in English literature - Hasan, A. M. M. Mahmudul (Journal of Language, Literature, Social and Cultural Studies, 2024)
This study explores the role of language and communication in English literature, focusing on how words influence meaning, shape perspectives, and express cultural values. The primary objectives are to analyze the communicative power of language in selected literary works, examining how stylistic and rhetorical devices are employed to evoke emotions, construct identities, and convey ideologies. The study utilizes a qualitative approach, employing textual analysis as the method of data collection. Literary texts, including poems and essays, were analyzed to investigate the interplay between language, discourse, and communication. Critical Discourse Analysis (CDA) was applied to assess the socio-cultural and ideological dimensions embedded within these texts. The findings reveal that language in English literature serves as a powerful tool for social influence, resistance, and identity formation. The study concludes that understanding the communicative power of words is essential in deciphering the deeper meanings and societal impacts conveyed through literature.